2019
DOI: 10.1136/bmjgh-2018-001133
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of evidence on public health in the Democratic People’s Republic of Korea

Abstract: BackgroundEngaging in public health activities in the Democratic People’s Republic of Korea (DPRK, also known as North Korea) offers a means to improve population health for its citizens and the wider region. Such an engagement requires an understanding of current and future needs.MethodsWe conducted a systematic search of five English and eight Korean language databases to identify available literature published between 1988 and 2017. A narrative review of evidence was conducted for five major categories (hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…(S.-K. Lee, 2017 ). Regarding the healthcare system in North Korea, the management of chronic diseases is neglected in North Korea as the government of North Korea has allotted only one research agenda on non-communicable diseases, i.e., mental health, and seven communicable disease-oriented policy agendas among 16 priorities in the Medium Term Strategic Plan 2016–2020 ( Park et al, 2019 ). This is similar to the healthcare system and policy in low- and middle-income countries ( Geneau et al, 2010 ), but demographic trends and population and disease burden composition paradoxically seem to be rather close to those of high-income and upper-middle-income countries ( Hong & Kim, 2021 ; E. H. Lee et al, 2022 ) (see Supplementary Appendix 9 ), which implies that an inadequate response to non-communicable diseases may cause a considerable disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…(S.-K. Lee, 2017 ). Regarding the healthcare system in North Korea, the management of chronic diseases is neglected in North Korea as the government of North Korea has allotted only one research agenda on non-communicable diseases, i.e., mental health, and seven communicable disease-oriented policy agendas among 16 priorities in the Medium Term Strategic Plan 2016–2020 ( Park et al, 2019 ). This is similar to the healthcare system and policy in low- and middle-income countries ( Geneau et al, 2010 ), but demographic trends and population and disease burden composition paradoxically seem to be rather close to those of high-income and upper-middle-income countries ( Hong & Kim, 2021 ; E. H. Lee et al, 2022 ) (see Supplementary Appendix 9 ), which implies that an inadequate response to non-communicable diseases may cause a considerable disease burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to improve the awareness of health behaviors and disease status on CVD among North Koreans defectors. However, a recent review showed that the majority of NCD studies on North Korean defectors addressed mental health issue [39].…”
Section: Discussionmentioning
confidence: 99%
“…'Koryo Medicine' was excluded from the analysis despite the North Korean traditional approach to the field of psychiatry, as the research articles were only available from 2016 forward. Publications from international, peer‐reviewed journals were not included as North Korean studies on psychiatric topics are scarcely introduced outside the country (Jeong & Choi, 2018; Park, Lim, et al, 2019).…”
Section: Methodsmentioning
confidence: 99%